Abnormality of Klotho Signaling Is Involved in Polycystic Ovary Syndrome. (March 2018) - Mao, Zenghui; Fan, Liqing; Yu, Qiao; Luo, Shuwei; Wu, Xianling; Tang, Jun; Kang, Gehua; Tang, Le
This study investigated the involvement of the klotho-associated signaling in the apoptosis of granulosa cells (GCs) from the ovaries of patients with polycystic ovary syndrome (PCOS) and PCOS animals. Primary GCs were obtained from 26 healthy women and 43 women with PCOS. The PCOS animal model was established by the injection of dehydroepiandrosterone (DHEA). Klotho protein and associated microRNA expression in human primary GCs and rats' ovarian tissues were measured by Western blot and real-time polymerase chain reaction, respectively. Results showed that significantly lower miR-126-5p and miR-29a-5p microRNA expressions, higher klotho protein expression, lower insulin growth factor 1 (IGF-1R) and Wnt family member 1 (Wnt1) protein expressions, and lower Akt phosphorylation at Ser 473 and Thr 308 residues were observed in the GCs from patients with PCOS and the ovarian tissues of PCOS rats compared to that in GCs from healthy women and ovarian tissues of normal control rats, respectively. Knockdown of klotho gene expression normalized IGF-1R and Wnt1 protein expressions and Akt phosphorylation in GCs from patients with PCOS and the ovarian tissues from PCOS rats; it also blocked the effects of insulin on apoptosis and proliferation in GCs from patients with PCOS and inhibited caspase-3 activity in ovarian tissues of PCOS rats. Knockdown of klotho gene expression increased the pregnancy rate in DHEA-treated female rats and increased the body weight of their newborns through normalizing the ovarian function and decreasing the formation of cystic follicles. In conclusion, the miR-126-5p, miR-29a-5p/klotho/insulin-IGF-1, Wnt, and Akt signal pathway may be involved in the apoptosis of GCs and subsequent development of PCOS.